2022
DOI: 10.19160/e-ijer.1058798
|View full text |Cite
|
Sign up to set email alerts
|

Uzaktan Eği̇ti̇m Süreci̇nde Scratch Programi Destekli̇ Öğreti̇mi̇n Akademi̇k Başari İle Öğrenmedeki̇ Eri̇şi̇ Ve Kalicilik Düzeyleri̇ne Etki̇si̇

Abstract: The purpose of this study is to reveal the effect of robotic coding-based Scratch programme supported teaching employed in the distance education process on students' academic achievement, attainment, and retention of learning levels. The study used "pretest-posttest control group design", a quasi-experimental design under experimental research method. The study group consists of 7th grade students attending Ali Elmacı Middle School in Yahyalı district of Kayseri province (Turkey) in the 2020-2021 academic yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Furthermore, it was also found that the lessons were more comprehensible and contributed to the student's active participation. In support of the results of the study, Şahbaz and Arseven (2022) found in their study that Scratch program-supported teaching had a positive effect on the academic success and learning levels of the students. Dikkartin Övez and Sezginsoy Şeker (2022), on the other hand, established in their study that students' motivation towards materials prepared with augmented reality technology and their attitudes towards these applications were at a very high level.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 56%
“…Furthermore, it was also found that the lessons were more comprehensible and contributed to the student's active participation. In support of the results of the study, Şahbaz and Arseven (2022) found in their study that Scratch program-supported teaching had a positive effect on the academic success and learning levels of the students. Dikkartin Övez and Sezginsoy Şeker (2022), on the other hand, established in their study that students' motivation towards materials prepared with augmented reality technology and their attitudes towards these applications were at a very high level.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 56%
“…Bu durum ise eğitim alanında bilgi kaynaklarının, fikirlerin ve ürünlerin dolaşımını hızlandırarak uluslar arasında küresel bir eğitim ağının temellerinin atılmasına öncülük etmiştir. Öte yandan eğitim alanındaki gelişmeler yalnızca kaynakların ve fikirlerin dolaşımı noktasında olmamış; geleneksel eğitim metotlarından (Şahbaz ve Arseven, 2022), öğretmen-öğrenci ilişkisine, ölçme ve değerlendirme yöntemlerinden (Bahar, 2014), ders araç ve gereçlerine, eğitimin felsefi temellerinden, eğitim kuramlarına kadar pek çok alanda köklü değişiklikler meydana getirmiştir. Bu noktada teknolojik gelişmelerle beraber eğitimde köklü dönüşümün yaşandığı konulardan biri de şüphesiz geleneksel öğretim materyallerinin yerini daha modern teknolojik araç-gereçlere bırakmasıdır.…”
Section: Introductionunclassified